Isolation, Identification, and Physiological Characterization of Indigenous Yeast Species Capable of Efficiently Utilizing Sugarcane Molasses as a Carbon Source - Sohail, Aamir; Ihsan, Kashmala; Khan, Raham Sher; Ali, Abid; Zia-ul Islam (Indus Journal of Bioscience Research, 2025)
Molasses, a byproduct of sugar production, contains sugars, ash, and inhibitors, limiting its microbial use. This study screened yeast species for efficient molasses utilization and inhibitor tolerance. Samples from four Khyber Pakhtunkhwa districts yielded 33 yeast strains after scrutiny. Following initial characterization, the strains were identified based on both morphological features and molecular methods involving the amplification of Internal Transcribed Spacer (ITS) regions. By the BLAST analysis, the ITS sequences for Candida tropicalis, Pichia kudriavzevii, Saccharomyces cerevisiae, Torulaspora delbrueckii, Trichosporon asahii, and Wickerhamomyces anomalus demonstrated 100% identity, whereas the sequence for Aspergillus fumigatus exhibited a maximum identity of 99.79% with the same species. In the phylogenetic analysis, these sequences were clustered with their respective corresponding species. Since molasses contain sucrose in major quantity, the physiological characterization of these isolated species in synthetic media containing sucrose as a sole carbon source reveals the higher growth efficiency of Torulaspora delbrueckii (OD600nm 5.24, μmax 0.0058 h-1) with second best performance of Trichosporon asahii (OD600nm 4.4, μmax 0.0049 h-1). The lowest grower was Saccharomyces cerevisiae (OD600nm 1.78 μmax 0.00016 h-1) while the remaining species i.e., Aspergillus fumigatus, Candida tropicalis, Pichia kudriavzevii, and Wickerhamomyces anomalus were of intermediate level (OD600nm 3.44, 3.89, 3.81, and 3.77, μmax was 0.0045 h-1, 0.0042 h-1, 0.0042 h-1, 0.0042 h-1 respectively). The isolated yeast species, known for utilizing non-molasses carbon sources, expand our understanding of substrate usage. Their potential as biofactories or genetic resources from natural evolution could aid in engineering industrial yeast strains for biofuel and biochemical production.